Tahap kefahaman dan praktik solat dalam kalangan masyarakat Orang Asli Kuala Boh, Tanah Tinggi Cameron Pahang, Malaysia / Habibah Ayob … [et al.] - Ayob, Habibah; Othman, Che Noriah; Hamzah, Halipah; Karjanto, Suryaefiza (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2015)
This study aims to identify the level of understanding and the prayers practices among indigenous communities of Kuala Boh, Cameron Highlands, Pahang, Malaysia. The methodology used in this research is a case study through questionnaires and observations from house to house. Respondents in the village were evaluated about the level of awareness and understanding of prayers through questionnaires and observations. They were randomly selected to demonstrate the ways of prayers. This observation was recorded for further analysis. Guidelines on the practice of prayers accuracy was based on Islamic teaching. The data obtained was analyzed and presented in the form of a percentage of the graphs and pie charts. There were 29 respondents who participated in this research. Most respondents had a minimum level of understanding and practicing prayer. Most of the respondents knew about the law of prayer, love and realize the benefits of prayer. Most respondents practice five daily prayers. Most of them, also knew about ablutions, action in prayers and the recitations in prayers. However, the level of their knowledge and skills in prayers need to be improved. The conclusion from this study is the level of knowledge and practical accuracy of prayers among the Orang Asli Kuala Boh should be improved. Programs to improve the understanding and practice of prayer should be conducted as a religious and social responsibility by the authorities.